Advances in Intelligent Informatics - El-Alfy, El-Sayed M.; Thampi, Sabu M.; Takagi, Hideyuki; Piramuthu, Selwyn; Hanne, Thomas (Advances in Intelligent Systems and Computing, 2015)
This book contains a selection of refereed and revised papers of Intelligent Informatics Track originally presented at the third International Symposium on Intelligent Informatics (ISI-2014), September 24-27, 2014, Delhi, India. The papers selected for this Track cover several intelligent informatics and related topics including signal processing, pattern recognition, image processing data mining and their applications.